Microscale methods to rapidly evaluate bioprocess options for increasing bioconversion yields: application to the ω-transaminase synthesis of chiral amines - Halim, Murni; Rios-Solis, Leonardo; Micheletti, Martina; Ward, John Montgomery; Lye, Gary J. (Springer, 2014)
This work aims to establish microscale methods to rapidly explore bioprocess options that might be used to enhance bioconversion reaction yields: either by shifting unfavourable reaction equilibria or by overcoming substrate and/or product inhibition. As a typical and industrially relevant example of the problems faced we have examined the asymmetric synthesis of (2S,3R)-2-amino-1,3,4-butanetriol from l-erythrulose using the ω-transaminase from Chromobacterium violaceum DSM30191 (CV2025 ω-TAm) and methylbenzylamine as the amino donor. The first process option involves the use of alternative amino donors. The second couples the CV2025 ω-TAm with alcohol dehydrogenase and glucose dehydrogenase for removal of the acetophenone (AP) by-product by in situ conversion to (R)-1-phenylethanol. The final approaches involve physical in-situ product removal methods. Reduced pressure conditions, attained using a 96-well vacuum manifold were used to selectively increase evaporation of the volatile AP while polymeric resins were also utilised for selective adsorption of AP from the bioconversion medium. For the particular reaction studied here the most promising bioprocess options were use of an alternative amino donor, such as isopropylamine, which enabled a 2.8-fold increase in reaction yield, or use of a second enzyme system which achieved a 3.3-fold increase in yield.